Playing cultures - Moon, P; Derby, M (Te Ara Poutama - the Faculty of Maori and Indigenous Development, Auckland University of Technology, 2018)
The genesis of this article is a series of observations that occurred at a marae, which are used here as a platform from which broader issues of certain aspects of Māori-Pākehā interactions can be explored and critiqued. The trajectory of biculturalism and its accompanying narrative – as a linear progression of mutual engagement between Māori and Pākehā – has been an accepted orthodoxy in this discourse for decades, with the extent, character, and form of engagement being among the principal points of focus for consideration. However, what is examined here is a radically different interpretation to this approach to biculturalism. The main reason for this is that much of the discourse around biculturalism bypasses the risks for indigenous cultural marginalisation that these narratives have the potential to cause. It is further argued here that there can be an element of racism within the practice of biculturalism that is not merely incidental, but rather functions as one of its central operating principles. This work is necessarily impressionistic in the manner in which it tackles the issues under review. The aim here is not to be comprehensive, nor to question anyone’s goodwill in the realm of biculturalism. Rather, it is to sift through some of the elements that comprise current iterations of Pākehā roles in bicultural interactions with Māori. One of the central themes that runs through this survey is the dimensions of power relationships and indigenous agency in these interactions, and their potential implications for interpreting aspects of biculturalism. In particular, the possibility is explored here that beneath the goodwill and overtly positive intentions that typify Pākehā engagement with Te Ao Māori is an intricate web of cultural power relationships that unwittingly perpetuate a pattern of Pākehā cultural domination. The starting point for this analysis is the notion, in the most general sense, of a Pākehā (or more specifically, Anglo-Saxon) cultural deficit existing in the country. What is proposed here is that one of the consequences of this is a particular (and predictable) set of reactions that are borne of a people experiencing this deficit. Of course, these are substantial simplifications, and are acknowledged here from the outset as such. However, the fact that they are generalisations does not necessarily diminish the insights they potentially offer in the area of New Zealand’s distinct bicultural environment. From this point, the cultural customs of pōwhiri and pepeha are used as a starting point from which the intricate web of cultural integration, overlap, and encounter can begin to be disentangled. Consideration is given to the dynamic that exists between te reo Māori and English, where the incorporation of Māori words into the English lexicon is, in fact, playing a key role in destroying the indigenous language. The role of Kaupapa Māori research methodologies is also reviewed, as an example of neo-colonialism wrapped up as a concept that allegedly empowers Māori. This work concludes by questioning many of the presumptions currently held about the utility of Pākehā engagement with Te Ao Māori. In particular, it sheds light on the ways in which what can superficially appear as favourable types of bicultural engagement have the potential, to the same extent, to entrench structures of Pākehā cultural domination. We deliberately do not offer any prescription for an alternative, but simply state these observations as a base from which further analyses can be carried out, and from which these interactions can be re-contextualised.